2011
DOI: 10.1128/jb.05899-11
|View full text |Cite
|
Sign up to set email alerts
|

CodY-Mediated Regulation of Guanosine Uptake in Bacillus subtilis

Abstract: CodY is a global transcriptional regulator known to control expression of more than 100 genes and operons in Bacillus subtilis. Some of the most strongly repressed targets of CodY, the nupNOPQ (formerly, yufNOPQ) genes, were found to encode a guanosine transporter. Using DNase I footprinting experiments, we identified two high-affinity CodY-binding sites in the regulatory region of the nupN gene. The two sites are located 50 bp upstream and 163 bp downstream of the transcription start site. The downstream site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…1B). In general, nonspecific binding of CodY in gel shift experiments is observed only at 400 to 800 nM CodY (45,50). Confirming the specificity of interaction, DNase I footprinting experiments showed that CodY protected a single region of DNA, located at positions ÏȘ7 to Ï©30 with respect to the aprE transcription start point (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…1B). In general, nonspecific binding of CodY in gel shift experiments is observed only at 400 to 800 nM CodY (45,50). Confirming the specificity of interaction, DNase I footprinting experiments showed that CodY protected a single region of DNA, located at positions ÏȘ7 to Ï©30 with respect to the aprE transcription start point (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…First, most known mechanisms regulate the de novo pathway; (p)ppGpp blocks both de novo and salvage GTP biosynthesis, globally regulating GTP production from all sources. Second, transcriptional feedback mechanisms that regulate GTP biosynthesis genes (Ebbole and Zalkin, 1989; Belitsky and Sonenshein, 2011) may not prevent accumulation of GTP as rapidly as direct enzymatic inhibition by (p)ppGpp. Third, previously known mechanisms of GTP homeostasis involve only precursors and intermediates of purine biosynthesis; pppGpp is an off-pathway product synthesized from GTP to provide a negative feedback loop (Figure 3B).…”
Section: Discussionmentioning
confidence: 99%
“…One possible downstream effector is the transcriptional regulator CodY. CodY is activated by GTP and branched-chain amino acids, represses stationary-phase and guanosine transporter genes, and induces expression of guaB (20,22,35,36). Therefore, it is possible that the effect of guanosine/GTP level on growth rate requires CodY activity.…”
Section: Resultsmentioning
confidence: 99%